Donor-But Not Recipient-Derived Cells Produce Collagen-1 in Chronically Rejected Cardiac Allografts - Balam, Saidou; Buchtler, Simone; Winter, Frederike; Schmidbauer, Kathrin; Neumayer, Sophia; Talke, Yvonne; Renner, Kerstin; Geissler, Edward K.; Mack, Matthias (Frontiers in Immunology, 2022)
Fibrosis is a prominent feature of chronic allograft rejection, caused by an excessive production of matrix proteins, including collagen-1. Several cell types produce collagen-1, including mesenchymal fibroblasts and cells of hematopoietic origin. Here, we sought to determine whether tissue-resident donor-derived cells or allograft-infiltrating recipient-derived cells are responsible for allograft fibrosis, and whether hematopoietic cells contribute to collagen production. A fully MHC-mismatched mouse heterotopic heart transplantation model was used, with transient depletion of CD4+ T cells to prevent acute rejection. Collagen-1 was selectively knocked out in recipients or donors. In addition, collagen-1 was specifically deleted in hematopoietic cells. Tissue-resident macrophages were depleted using anti-CSF1R antibody. Allograft fibrosis and inflammation were quantified 20 days post-transplantation. Selective collagen-1 knock-out in recipients or donors showed that tissue-resident cells from donor hearts, but not infiltrating recipient-derived cells, are responsible for production of collagen-1 in allografts. Cell-type-specific knock-out experiments showed that hematopoietic tissue-resident cells in donor hearts substantially contributed to graft fibrosis. Tissue resident macrophages, however, were not responsible for collagen-production, as their deletion worsened allograft fibrosis. Donor-derived cells including those of hematopoietic origin determine allograft fibrosis, making them attractive targets for organ preconditioning to improve long-term transplantation outcomes.